Enzimatic Kinetics of Cellulose Hydrolysis using Cellulase from Goat Rumen Fluids - Gunawan Wijonarko; Ike Sitoresmi Mulyo Purbowati; Ali Maksum (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
In line with the depletion of petroleum reserves from fossils, humans have forced people to look for alternative renewable energy sources. Nipah plant stems are organic material that contains a lot of lignocellulose. Cellulose in lignocellulose can be hydrolyzed to glucose to produce bioethanol. Problems arise because hydrolysis using pure cellulase requires relatively high costs, so it is necessary to find an alternative source of cheap cellulase. One of the cheap sources of cellulase is goat rumen fluid. Until now, there is not much information regarding the reaction kinetics and cellulase characteristics of goat rumen fluid. The purpose of this study was to isolate crude cellulase extract, determine the KM and Vmax values ​​and determine the optimum temperature and pH. The research was carried out at the Unsoed Agricultural Technology Laboratory. The samples used were seven rumen fluids. The study began with isolation followed by enzymatic kinetics studies. Fractionation was carried out by adding ammonium sulfate salt (50, 60,70, and 80 %), and centrifugation at 7,000 rpm at 4 oC for 15 minutes. Crude cellulase extract with the highest enzyme activity value was used for the study of enzymatic reaction kinetics and characterization. The crude cellulase resistance test to temperature was carried out at 45, 55 and 65 oC and the pH was carried out at pH 4, 5, 6, 7 and 8. The KM and Vmax values ​were determined by measuring the activity of crude cellulase extract at various concentrations of CMC (1, 1 ,5, 2, 2.5, and 3 %). The results showed that crude cellulase extract had an average specific activity of 1.7356 IU/mg. The highest enzyme activity was 0.9854 IU/ml. The optimum crude cellulase extract was at pH 6 with an activity of 1.1015 IU/ml and a temperature of 60 oC with an activity of 0.7829 IU/ml. At a CMC concentration of 2.5% crude cellulase extract had an activity of 0.3179 IU/ml with a Vmax value of 0.0045 IU/ml and a KM of 0.0252 %.